2014
DOI: 10.7727/wimj.2014.036
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Parameters (Salivary Flow, pH and Buffering Capacity) in Stimulated Saliva of Mexican Elders 60 Years Old and Older

Abstract: These exploratory data add to the body of knowledge with regard to chewing-stimulated salivary features (salivary flow rate, pH and buffer capacity) and outline the variability of those features across selected sociodemographic, socio-economic and behavioural variables in a group of Mexican elders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 30 publications
4
32
1
1
Order By: Relevance
“…It is known that the vast majority of older people present physiological salivary reduction, tooth loss, use prostheses, use long-term medications and are affected by chronic degenerative diseases. However, the 65-year-old diabetic patients assessed in the present research showed sialometric values lower than those found in studies with diabetic and non-diabetic individuals aged 60 [ 34 , 35 ].…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…It is known that the vast majority of older people present physiological salivary reduction, tooth loss, use prostheses, use long-term medications and are affected by chronic degenerative diseases. However, the 65-year-old diabetic patients assessed in the present research showed sialometric values lower than those found in studies with diabetic and non-diabetic individuals aged 60 [ 34 , 35 ].…”
Section: Discussioncontrasting
confidence: 94%
“…Older people who presented hyposalivation also presented a smaller number of teeth compared to a group of older people with normal salivation [ 10 ]. Older people with greater tooth loss and who use prostheses also suffer a decrease in salivary flow [ 34 ]. The failure in masticatory rehabilitation is a factor that can enhance hyposalivation.…”
Section: Discussionmentioning
confidence: 99%
“…The group meets three days a week in the city of Pachuca, in the Hidalgo province of Mexico, for recreation, culture and entertainment. The study design and subjects have been described in detail17181920. Briefly, a cross-sectional study was conducted.…”
Section: Methodsmentioning
confidence: 99%
“…Es un grupo donde se realizan actividades de recreo, culturales y de esparcimiento, y se reúnen 3 días por semana. Parte de la metodología ha sido previamente publicada 18,19 . Brevemente, se realizó un estudio de diseño transversal (observacional).…”
Section: Materials Y Métodos Diseño Y Muestra Del Estudiounclassified